A Fast Strategy to determine the Physical and Electrical Parameters of Photovoltaic Silicon Cell - El Hadi Chahid; Mohammed Idali Oumhand; Abdessamad Malaoui (Institute of Advanced Engineering and Science, 2017)
This paper proposes a fast strategy to extract and exploit the electrical parameters of photovoltaic cell using the double-diode model. The polycrystalline silicon (poly-Si) junction is chosen in this work due to the importance of its proprieties in industrial and economic fields. The proposed method to extract the solar cell electrical parameters contains two steps. The first is based on the graphical adjustments to choose the initial values of these parameters, and the second is numerical, using Modified Newton-Raphson’s algorithm. The obtained parameters extractions values are compared to the others methods and give a considerable agreement. Furthermore, we have developed a complementary analytical method to deduce both the minority’s carrier’s lifetime and the diffusion lengths through the diffusion and recombination current densities. The found values of these parameters are precisely comparable with theoretical models, and give very useful informations on the intrinsic quality of the studied cell.